Faktor Pendorong Praktik Perkawinan Anak Di Desa Taman Baru, Kecamatan Sekotong - Sherly Kurnia Dafani; Maya Atri Komalasari; Hafizah Awalia (Multikultural: Jurnal Ilmu Sosial, 2023)
Child marriage is a marriage performed under the age permitted to marry. Although various regulations have been made, the number of child marriages each year has not decreased significantly. Related to this, the factors that underlie child marriage actors in carrying out child marriage practices can be a reference in answering this problem. This study aims to find out what are the factors that encourage youth to practice child marriage in Taman Baru Village, Sekotong District, West Lombok Regency. The research method used is qualitative with a phenomenological research design. The unit of analysis in this study is an individual who knows about the issue of child marriage. The subject collection technique used was purposive sampling. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is condensation, data presentation, and drawing conclusions. In testing the validity of the data, this study used a source triangulation technique. The results of the study show that the factors that encourage youth to practice child marriage consist of internal and external factors. Internal factors include because of their own desires; External factors include parental factors, partner factors, economic factors, traditional factors, friendship environmental factors, religious factors, and internet factors.